Does Halal Certification Matter? The Influence of Polarity in Religious Understanding on Attachment to Halal Certification in Indonesia - Dzukroni, Arisy Abror; Raharjo, Raharjo (Universitas Islam Internasional Indonesia, 2025)
This article examines the influence of polarity in religious understanding on attachment to halal certification in Indonesia. In 2024, there were 3,237,167 products that have been certified halal, with 58.5% being self-declared as halal and the remaining 41.5% being regular halal certificates. This number has more than tripled since 2019, when there were just 963,411 halal-certified products. The high increase in the number of halal-certified products is directly proportional to the high halal awareness of Indonesian Muslims. Previous studies have not explicitly addressed the concept of halal as understood by the Indonesian Muslim community, which possesses a diverse range of religious interpretations. This article reveals the typology of Indonesian Muslim religious understanding and its influence on attachment to halal certification. This research used quantitative methods by distributing questionnaires to Indonesian Muslim respondents with conservative, moderate, and progressive religious categorizations. Respondents in this study were aged 18-60 years, and included both men and women. Data were analyzed using the ANOVA technique using SPSS 29.0.1. The results show a significant value (0.008), indicating a difference in attachment to halal certification between conservative, moderate, and progressive groups, with the highest attachment average amongst conservative Muslims (33.46).